2021
DOI: 10.3389/fimmu.2021.594356
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Exercise Are Major Determinants of Natural Killer Cell Activity, Which Is Age- and Gender-Specific

Abstract: BackgroundThe coronavirus-19 disease (COVID-19) pandemic reminds us of the importance of immune function, even in immunologically normal individuals. Multiple lifestyle factors are known to influence the immune function.ObjectiveThe aim was to investigate the association between NK cell activity (NKA) and multiple factors including vitamin D, physical exercise, age, and gender.MethodsThis was a cross-sectional association study using health check-up and NKA data of 2,095 subjects collected from 2016 to 2018 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 78 publications
0
17
1
Order By: Relevance
“…Micronutrient supplementation in early gestation has gender-differential effects on the immune system in offspring, particularly on an epigenetic level [ 55 ]. Vitamin D modulates the activity of natural killer cells in a gender-dependent manner [ 56 ], presumably via the molecular interaction between estrogen and vitamin D [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Micronutrient supplementation in early gestation has gender-differential effects on the immune system in offspring, particularly on an epigenetic level [ 55 ]. Vitamin D modulates the activity of natural killer cells in a gender-dependent manner [ 56 ], presumably via the molecular interaction between estrogen and vitamin D [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…This novel assay uses the serum of ex vivo-stimulated whole blood to detect secreted IFN-γ from NK cells as an indicator of NKA [ 8 ]. Using this method, clinical studies have indicated that NKA is a useful marker for different cancers and is related to immunologic conditions such as aging and vitamin D insufficiency [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Beyond broad actions to ameliorate ILCs’ function [ 147 , 148 ], interest has emerged on ILC metabolism as a therapeutic target [ 149 , 150 ]. While these enhancements are not specifically directed towards the treatment of MM, CD38 knockout via CRISPR/Cas9 resulted in higher mitochondrial respiratory activity, with improved persistence in ex vivo expanded peripheral blood NK cells directed against MM cells [ 134 ].…”
Section: Targeting Innate Lymphoid Cells For Multiple Myeloma Immunotherapymentioning
confidence: 99%